Strategy of satellite monitoring of organic carbon content in arable soil horizons in Russia - I. Yu. Savin; E. Yu. Prudnikova; G. V. Windecker; N. S. Sobolev (Бюллетень Почвенного института им. В.В. Докучаева)
The world has accumulated quite a lot of experience in remote assessment of organic carbon content in soils. But, except for rather schematic global approaches, monitoring at the detailed level is still localized, and the constructed models cannot be extrapolated to other territories. The aim of the study was to develop a strategy for unified remote sensing monitoring of organic carbon content in arable soil horizons for the whole territory of Russia and to test it. The strategy is based on the analysis of Landsat 8-9 OLI satellite data archives. Regression models (linear or exponential) of the relationship between the reflectance of the open surface of soils in the near infrared range and the content of organic carbon in arable soil horizons are built on the basis of literature data and their parameters are selected individually for each unit of the country regionalization, which is the geometric part of the Unified State Register of Soil Resources of Russia. On the basis of models, a base map of carbon content in arable soil horizons for a period of five years was constructed. After that, a map of carbon content at the end of the current year was built on the basis of the same methodological approaches. Comparison of the maps allows estimation of changes in the current year relative to the base period. Demonstration of the use of this approach was carried out for two contrasting regionalization units in the Tver and Tula regions of Russia. The approach showed low, but comparable to analogs, accuracy for detecting small changes in carbon content (prediction error was 0.8–1.0%), but allowed to confidently identify areas with abrupt changes. It is assumed that the accuracy of modeling will increase annually with the accumulation of field data on carbon content in the arable horizon of soils, as well as with the refinement of models in each regionalization unit. Such an approach can be used to organize annual remote sensing monitoring of carbon content changes in arable soils within the framework of climate projects of the country.